Pengaruh Konsentrasi Rootone-F terhadap Pertumbuhan Setek Pucuk Akasia ((Acacia crassicarpa A. Cunn. Ex Benth) - Hazmi, Wahyu; Armaini, Armaini; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Acacia is generally propagated by cuttings, shoots for genetic preservation and production of large numbers of seedlings. The problem with planting acacia is when seeding cuttings. The critical period for cutting cuttings is when the cuttings have not yet taken root, while the formation of shoots requires active growth of the roots, so that during this period the number of cuttings that die during sowing is very high. The fix can be done by giving Rootone-F which is a growth regulator of the auxin type, which can stimulate and accelerate the rooting of cuttings. This study aims to determine the effect and obtain the best concentration of Rootone-F for the growth of acacia shoot cuttings. This study used a randomized block design (RBD) with five concentrations of Rootone-F treatment, namely: 0 ppm (control), 100 ppm, 200 ppm, 300 ppm, and 400 ppm. The results showed that the administration of Rootone-F had an effect on the growth of seedling height and number of leaves. Giving Rootone-F concentration of 100 ppm is the best treatment that supports the growth of acacia cuttings. Key words: Acacia, Shoot cuttings, Rootone-F, Plant regulation